2021
DOI: 10.36076/ppj.2021/24/e327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thoracic Epidural Access with Lateral Decubitus and Shoulder Rotation Positions for Repeat Thoracic Epidural Blockade

Abstract: Background: Shoulder rotation has been shown to increase the acoustic window of ultrasound for thoracic epidural access. However, this effect of shoulder rotation has not yet been confirmed in clinical practice. Objective: This study aimed to evaluate the effects of shoulder rotation on the thoracic epidural blockade in patients with acute or chronic pain in the thoracic region. Study Design: Prospective crossover trial. Setting: Pain clinic of our university in the Republic of Korea. Methods: Forty patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Although the anteroposterior view and LAT view are widely used as standard practice, recent attention has been directed towards using the CLO view for identifying the needle depth during the fluoroscopic-guided interlaminar epidural access 23. The CLO view appears to be a feasible alternative to the traditional fluoroscopic views for epidural access 4 7 24. Through scientific geometric analyses of the CLO view, Gill et al suggested that fluoroscopic CLO views at 50° and 45° were proper in the cervical and lumbar regions, respectively, to improve needle tip visualization and provide a consistent landmark when accessing the epidural space 4 7.…”
Section: Discussionmentioning
confidence: 99%
“…Although the anteroposterior view and LAT view are widely used as standard practice, recent attention has been directed towards using the CLO view for identifying the needle depth during the fluoroscopic-guided interlaminar epidural access 23. The CLO view appears to be a feasible alternative to the traditional fluoroscopic views for epidural access 4 7 24. Through scientific geometric analyses of the CLO view, Gill et al suggested that fluoroscopic CLO views at 50° and 45° were proper in the cervical and lumbar regions, respectively, to improve needle tip visualization and provide a consistent landmark when accessing the epidural space 4 7.…”
Section: Discussionmentioning
confidence: 99%